(untitled) - Francesco, Costanzo (New York, 2010)
This book emphasizes critical thinking by presenting the reader with engineering situations. Compelling photorealistic art, and a robust photograph program helps readers to connect visually to the topics discussed.
Keywords: Mechanics, Applied,Cơ khí- Ứng dụng; Textbooks,Giáo trình